Psychopathological networks: Theory, methods and practice. (February 2022) - Bringmann, Laura F.; Albers, Casper; Bockting, Claudi; Borsboom, Denny; Ceulemans, Eva; Cramer, Angélique; Epskamp, Sacha; Eronen, Markus I.; Hamaker, Ellen; Kuppens, Peter; Lutz, Wolfgang; McNally, Richard J.; et al.
Abstract: In recent years, network approaches to psychopathology have sparked much debate and have had a significant impact on how mental disorders are perceived in the field of clinical psychology. However, there are many important challenges in moving from theory to empirical research and clinical practice and vice versa. Therefore, in this article, we bring together different points of view on psychological networks by methodologists and clinicians to give a critical overview on these challenges, and to present an agenda for addressing these challenges. In contrast to previous reviews, we especially focus on methodological issues related to temporal networks. This includes topics such as selecting and assessing the quality of the nodes in the network, distinguishing between- and within-person effects in networks, relating items that are measured at different time scales, and dealing with changes in network structures. These issues are not only important for researchers using network models on empirical data, but also for clinicians, who are increasingly likely to encounter (person-specific) networks in the consulting room. Highlights: The network approach brings a new view on mental disorders Methodological and practical challenges hamper moving from theory to clinical research These challenges include, for example, the use of nodes with different time scales This paper extensively discusses both these challenges and possible solutions This will help to overcome current limitations in using networks in clinical psychology